The Importance of Business Ethics to Enhance Corporate Social Responsibility - Abdul Wahid Mahsuni (International Journal of Economics, Commerce, and Management, 2025)
In an increasingly complex era of globalization, companies are expected not only to be profit-oriented, but also to pay attention to their social responsibility. This study aims to analyze the effect of business ethics on the effectiveness of Corporate Social Responsibility (CSR) programs in companies listed on the Indonesia Stock Exchange (IDX). The method used is quantitative analysis with a Structural Equation Modeling (SEM) approach using data from questionnaires distributed to 100-150 companies during the 2019-2023 period. The results of the analysis show that there is a significant relationship between business ethics and CSR performance, where companies that apply ethical principles tend to have more effective CSR programs. The implications of this study emphasize the importance of integrating ethics in business strategy to enhance corporate reputation and meet stakeholder expectations. This study also provides recommendations for companies and policy makers to formulate policies that support ethics-based CSR practices.